Nutrient intake in high performance show-jumping horses in France - Martin, Lucile; Geffroy, A; Bonneau, A; Barré, C; Nguyen, P; Dumon, H (MTT, 2008)
The nutrient requirements of athletic horses are closely dependent on workload and need to be defined for each discipline. As only few surveys have focused on show-jumping, the aim of the present work was to describe dietary practices in elite show-jumpers in France and compare them with the NRC 2007 recommendations. Seventeen horses (12 stallions, 3 mares, 2 geldings; age 12±1 y; BW 591±13 kg) were included in the study. Their feeds were analysed and their general health, feeding schedule and meal composition were recorded. All data were expressed as mean ± SEM. Mean digestible energy (DE) intake was 1.4±0.1 times the maintenance requirement but varied considerably (from 1.0 to 1.9) with no effect of gender. Crude protein (CP) intake ranged from 84 to 147 % of the recommendations for exercise horses, with a mean CP:DE ratio of 45±8 g/MCal DE. Mineral intake exceeded the recommendations, except for sodium and chloride. Body condition was satisfactory in all horses indicating that energy intake met the energy requirement for maintenance plus exercise, despite large variations between animals. Mineral intake varied widely, and in most cases, the actual intake made any supplementation, especially of calcium, unnecessary. Our results emphasize 1) the imbalanced diets compared to current recommendations and 2) the similar performances of the horses despite the different diets offered to them. They also show that the variation in workload, within a single athletic discipline, may be wide.
Keywords: Ko; horse; nutrients; balance; show jumper